Marketing and Technology: A Strategic Coalignment - Capon, Noel; Glazer, Rashi (Journal of Marketing, 1987)
The authors present a case for integrating technology and marketing strategy as key elements that affect corporate success in rapidly changing environments. After describing the implications of technological change for firm behavior, the authors propose a framework for developing a technology strategy and introduce the technology portfolio. The technology portfolio serves both as a model for technological resource allocation and as an aid in choosing an optimal set of technologies from a set of feasible alternatives.